Dystonia in atypical parkinsonian disorders. (September 2019) - Marsili, Luca; Bologna, Matteo; Kojovic, Maja; Berardelli, Alfredo; Espay, Alberto J.; Colosimo, Carlo
Abstract: Dystonia is common in the classic atypical parkinsonian disorders such as multiple system atrophy, progressive supranuclear palsy and corticobasal degeneration, and to a lesser extent in dementia with Lewy bodies. Its clinical phenomenology, including body distribution, timing of appearance, severity, and relationship to dopaminergic and other medications may vary considerably within and between atypical parkinsonian disorders. From a pathophysiological standpoint, the coexistence of dystonia with parkinsonism challenges the functional model of the basal ganglia. Clinical recognition of specific dystonic features may assist in the differential diagnosis of atypical parkinsonian disorders and in distinguishing them from Parkinson's disease. The presence of dystonia in atypical parkinsonian disorders informs management decisions. Reduction or withdrawal of levodopa should be considered if there is a close relationship between the onset of dystonia with periods of high dopaminergic tone. Botulinum neurotoxin may be considered in focal presentations. We here provide an updated overview of dystonia arising in the setting of atypical parkinsonian disorders, summarizing relevant clinical and clinicopathological studies, underlying pathophysiological mechanisms, diagnostic clues and potential pitfalls in the diagnosis. Finally, we suggest a tailored therapeutic approach for the management of these patients. Highlights: Dystonia is a common feature of atypical parkinsonian disorders. Dystonia patterns assist in the differential diagnosis of parkinsonisms. Body distribution and relationship with dopaminergic medication can be distinctive. Therapies include reduction of dopaminergic medications and botulinum neurotoxin.